UPAYA MENINGKATKAN PENGELOLAAN SAMPAH MELALUI PENDEKATAN KONTEKSTUAL - Luthfia Aldila Arsy Subagyo; Dian Eka Aprilia Fitria Ningrum (Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to increase student’s knowledge related to waste management through contextual approach. The subjects of this study were grade 3 students, as many as 28 students. This research was conducted at MI Perwanida Blitar. The research method used is in the form of Classroom Action Research (CAR) with Kemmis and Mc. Taggart went through two cycles, each cycle consists of planning, implementing, observing, and reflecting. The research instruments used were interview, written tests, and documentation. The results showed that student’s knowledge related to waste management through contextual approach in each cycle increased from 74% in the first cycle to 84% in the second cycle, so that the results of this study had reached the expected criteria. The application of contextual approach in learning waste management can help students to improve their knowledge in managing waste, both individually and in groups.